2019
DOI: 10.32674/jis.v0i0.675
|View full text |Cite
|
Sign up to set email alerts
|

Jeitinho as a Coping Strategy Used by Brazilian International Students for Acculturative Stress

Abstract: This mixed-method study examined whether Brazilian students in the US use an indigenous problem-solving practice, jeitinho, as a coping strategy for acculturative stress. Forty-two participants answered an online survey, which was a culmination of demographic information, the Acculturative Stress Scale for International Students, BriefCOPE, jeitinho questionnaire, and three open-ended questions about how Americans may perceive jeitinho. Results showed that a negative dimension of jeitinho was associated with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Other studies, including Go et al [15], Nishioka et al [16] and Quansah et al [30], have identified common challenges that extend beyond the scope of physical culture teachers and are prevalent among educators in various subject areas. Go et al [15] shed light on the significance of various coping strategies, including religion/mindfulness, social support from family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, including Go et al [15], Nishioka et al [16] and Quansah et al [30], have identified common challenges that extend beyond the scope of physical culture teachers and are prevalent among educators in various subject areas. Go et al [15] shed light on the significance of various coping strategies, including religion/mindfulness, social support from family members.…”
Section: Discussionmentioning
confidence: 99%
“…In student-related stressful situations, Go et al [15] identified religion/mindfulness, social support from family members, and self-blame as relevant emotional coping strategies. Similarly, Nishioka et al [16] found that nonadaptive coping strategies were associated with a negative dimension of jeitinho among Brazilian students, although it was not a significant predictor of acculturative stress. Additionally, Sagin [17] utilized a structural equation model and revealed a positive relationship between students' interest in physical education and their life satisfaction.…”
mentioning
confidence: 93%
“…Among culture-specific constructs, Brazilian jeitinho is particularly interesting for a variety of reasons. First, recent psychological studies have shown that the syndrome shows a more complex multi-dimensional structure, which can be linked to commonly studied psychological correlates such as values, personality, and ideology (Ferreira et al, 2012; Fischer et al, 2014; Miura et al, 2019; Nishioka and Akol, 2019; Resende and Porto, 2020). Second, previous sociological and ethnographic research has focused on the distinctiveness and salience of the construct within Brazil using observations and historical analyses (DaMatta, 1979), but psychological research has suggested that there is a disconnect between the normativeness of the construct at a symbolic level and the personal endorsement of individual behavioral facets (Ferreira et al, 2012; Fischer et al, 2014).…”
mentioning
confidence: 99%
“…Therefore, I have reviewed the literature regarding Brazilian migrants in other English-speaking countries. Mixed-methods research studied Brazilian international students in the United States (Nishioka & Akol, 2019). This study asserts that Brazilian international students frequently perceive a high cultural distance between Brazil and the United States.…”
Section: Brazilian Migrants' Mental Health In Aotearoa New Zealandmentioning
confidence: 99%
“…This study asserts that Brazilian international students frequently perceive a high cultural distance between Brazil and the United States. Brazilian international students reported feeling pressured to achieve good results and quickly adapt to their host country's culture, which could increase their levels of acculturative stress (Nishioka & Akol, 2019). Nevertheless, acculturative stress is not the only factor negatively impacting Brazilian migrants' mental health in the United States.…”
Section: Brazilian Migrants' Mental Health In Aotearoa New Zealandmentioning
confidence: 99%